Pengaruh Menghafal Al-Quran Terhadap Pembentukan Karakter Peserta Didik Di Roudhotul Atfal (RA) Jamiatul Qurra Cimahi - Aziz, Jamil Abdul (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2017)
Education is a means to continue to pursue the formation of human character fundamentally, bring individual changes to the roots. However, the problem to this day there are still many gaps between expectations and the reality in the world of education. Therefore, need to be implemented by the efforts of educational institutions to participate in preventing the growth of a negative character in the self-learners. In this case, Roudhotul Athfal Jamiatul Qurra wal Huffadz, Cimahi, West-Java create memorization program (Tahfidz) al-Quran for all students. Where Tahfidz program is believed to be very helpful in shaping the character of students. In this study, researchers used a correlational analysis method, with quantitative approach. Author correlating the results of a questionnaire about the program Tahfidz al-Quran (Variable X) with character formation of students' (variable Y). The population studied were all students of class B totaling 100 students. So the authors took a sample of 24% of the total population of 24 students. As for the data processing after data from the questionnaire obtained. Researchers using the formula 'r' Product Moment, researchers get results from the value of 'r' desirable is 0, 5560. The authors correlate the results of the robservation with rtable at 1% significance level of 0, 5560> 0, 515, and correlate well robservation with the rtable at the 5% significance level = 0, 5560> 0, 404. Because ro is greater than rt the null hypothesis which was rejected and the alternative hypothesis proposed by the researchers received. This means that there was an effect or a positive correlation between the program Tahfidz al-Quran (Variable X) with character formation of students' (variable Y).